The Effect of Covid-19 on Stock Return in the Indonesian Stock Exchange - Fitriyah, Nur; Bambang, Bambang; Mariadi, Yusli (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2023)
Many industries have been affected by Covid-19 where since March 2020 the Composite Stock Price Index (IHSG) for the Indonesia Stock Exchange has decreased because many investors sold their shares, especially during the PPKM policy period. The purpose of this study was to find out the cases of COVID-19 against the stock prices of the Indonesian government's policy phase in dealing with COVID-19 during PPKM 2021. The sample of this study was all companies using the panel data regression fixed effect model, this study confirmed that the daily increase in the number of cases Confirmed COVID-19 has a significant negative effect on daily stock returns. Even though this PPKM is the longest policy period among all policies, it does not affect the effectiveness of stock returns. Therefore, in order to help the stock market overcome the COVID-19 crisis pandemic and recover sustainably, the government must be more aggressive, such as extending the policy period and more strict in terms of policy implementation so as to suppress the virus outbreak to increase investor confidence